A systematic review and meta-analysis of physical activity interventions among colorectal cancer survivors. Issue 5 (12th October 2020) - Mbous, Yves Paul; Patel, Jayeshkumar; Kelly, Kimberly M
Abstract : Adherence to physical activity increased among colorectal cancer survivors whom participated in interventions that used behavioral theory. Abstract: With the growing number of colorectal cancer survivors (CRCS), theory-based, high-quality physical activity (PA) interventions are needed to promote quality and quantity of life. This systematic review and meta-analysis synthesized theory-based PA interventions among CRCS. Using PubMed, PsyINFO, CINAHL, MEDLINE, SportDiscus, and Cochrane databases, studies including CRCS participants, a PA outcome, a behavioral theory/model or behavior change techniques (BCTs), and randomized research design were identified. Two reviewers coded BCT, intervention reproducibility (Template for Intervention Description and Replication–TIDier), risk of bias, and quality of evidence. From an initial screen of 1, 328 articles, 10 RCTs met our inclusion criteria. The Transtheoretical Model ( n = 3), Social Cognitive Theory ( n = 3), and Theory of Planned Behavior ( n = 2) were the most used theories. "Goal setting (behavior)" ( n = 10), "goal setting (outcome)" ( n = 10), "action planning" ( n = 9), and "problem solving" ( n = 9) were the most commonly used BCTs. Intervention modalities were primarily print material based ( n = 4) and telephone counseling ( n = 4). Findings demonstrated that theory-based PA interventions are successful at increasing PA among CRCS as meta-analysis evidenced a small effect size of 0.26. TDier items 3, 9, and 12 hindered intervention replicability. Lack of blinding and bias in the measurement of outcomes by assessors resulted in serious bias. In-depth theoretical applications are needed for PA interventions that minimize bias and improve outcomes measurement. Intervention adherence and fidelity, as well as theoretical construct measurement pre- and post-intervention, will enhance the behavioral research enterprise. PROSPERO registration: CRD42019142816.